Is the Adventitial Vasa Vasorum in Vulnerable Carotid Plaques Increased or Decreased? - Wang Yixuan, Jin Lin, Chen Jianxiong, Yang Huixian, Shen Cuiqin, Xu Wenzhe, Shen Yuzhou, Huang Jun, Sun Liwan, Du Lianfang, Wang Bei, Li Fan, Li Zhaojun (Advanced Ultrasound in Diagnosis and Therapy)
Background Intraplaque neovascularization is a biomarker of vulnerable plaque. However, no data are available whether the increase in neovascularization within carotid plaques is a result of ischemia or an increase in adventitial vasa vasorum (VV). Objective To evaluate the VV signal in carotid vulnerable plaques. Methods Contrast-enhanced ultrasound (CEUS) examination was performed to examine changes in VV density in 47 patients with carotid plaque, and 21 patients received CT angiography (CTA) examination to assess the VV signal. In addition, a single-channel flow tissue model was fabricated for use in vitro studies to exclude pseudo-enhancement interferences in the distal wall of arteries by CEUS. Results The intensities of adventitial VV behind carotid plaque were lower than that of adventitial VV at the same level adjacent to the plaque in both CEUS and CTA examinations (P < 0.05). In vitro study, the intensities of far wall increased as the microbubble concentration increased (P < 0.05). However, no significant differences of intensities of far wall were found between different thicknesses tubes at the concentration of microbubble concentrations of 0.3% and 0.5% (P ≥ 0.05). Conclusion The formation of intraplaque neovascularization in carotid arteries is associated with the adventitial VV, and ischemia of VV may be a potential mechanism for intraplaque neovascularization.